Applications of super-resolution in photothermal imaging - Xu, D. (2013)
This paper focuses on applying Super-Resolution (SR) on Photothermal images of the 4.9μm Red Polystyrene Beads (RPB) obtained from a Photothermal imaging (PTI) system. Since the images acquired from the PTI system are noisy and it can be costly to achieve a higher resolution from the hardware side, it is efficient to do so by SR. In this paper, the experimental procedures are presented and the SR shows significant improvement in the processed images, mainly in terms of resolution, sharpness and contrast.